THE IMPACT OF SUPPLY CHAIN INTEGRATION ON SUPPLY CHAIN PERFORMANCE - Jahroni Jahroni; Moh Mukhsin; Diqbal Satyanegara (Universitas Nusa Cendana, 2025)
The objective of this study is to determine the impact of internal integration, supplier integration, and customer integration on supply chain performance. This research employs a quantitative method and uses a saturated sampling technique by distributing questionnaires to 67 SRC partners in Cilegon City. The analysis method used is SPSS V20. The findings indicate that internal integration, supplier integration, and customer integration positively and significantly impact supply chain performance. The adjusted R-squared value is 0.604, concluding that internal integration, supplier integration, and customer integration influence supply chain performance by 60.4%, with the remaining 39.6% influenced by other variables outside this study. Expanding the data scope and considering other factors are recommended to obtain more representative results. This is crucial for future research to provide a more comprehensive and accurate depiction of supply chain performance dynamics at SRC and in broader contexts. Keywords: Internal Integration; Supplier Integration; Customer Integration; Supply Chain Performance